P276 The Impact of the Optimum Patient Care Service on Outcomes for Adult Asthmatic Patients. (19th November 2012) - Ryan, D; Ryan, F; Mascarenhas, L; Saralaya, D; Britton, M; Ziegenweidt, J von; Burden, A; Hutton, C; Gould, S; David, P
Abstract : Introduction and Objectives: The Optimum Patient Care (OPC) service provides a comprehensive asthma assessment, analysing both GP-recorded and patient-reported outcomes to generate patient-specific management recommendations (based on British guidelines) for considerations by practise staff. This study evaluates the effect of the OPC asthma service evaluation on real-life asthma control outcomes in a UK primary care adult asthma population compared with a control population. Methods: Routine and patient-reported questionnaire data were collected for 2952 patients with clinician-diagnosed asthma and 1 year outcome data managed in practises across Surrey and Leicester County and Rutland Primary Care Trusts. The effect of the OPC service was evaluated by assessing change in markers of asthma control between initiation and re-assessment: exacerbation frequency (Read code defined acute exacerbations and number of courses of acute oral steroids in previous 12 months) and risk status (high risk: ≥2 annual exacerbations). The number of OPC management suggestions implemented by each practise was also considered. Change in exacerbations over the 12 month period was compared with a control group of patients from UK practises who did not receive OPC management recommendations. Exacerbation rate ratios (RR) for treatment group were produced (relative to control), adjusted for baseline confounders (95%CI). Results: There were 2952 patients in the study from 22 practises. At time of re-assessment 10% of OPC management suggestions had been implemented and 22% of patients managed at British Thoracic Society (BTS) steps 4/5 had improved their risk status. 17.1% of patients in the control group (n=22, 952) suffered from ≥1 exacerbation during the baseline year, increasing to 17.3% of patients after 12 months. For patients receiving the OPC management review, 24.8% had ≥1 exacerbation during baseline, decreasing to 15.3% following review. Conclusions: OPC's combined patient-reported and practise data assessment allowed thorough patient assessment and the generation of tailored management recommendations. Although only 10% of recommendations were implemented at 12 months, the OPC service appeared to have a beneficial effect on risk status and exacerbation rates.